The Comparison of Students Mathematics Learning Outcomes Between Using Performance Assessment and Self-assessment - Hernita Octaviani Putri; Jamali; Arif Muchyidin (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
A good assessment covers three aspects: cognitive, affective, and psychomotor. Many teachers tend to assess only the cognitive aspect. This problem requires treatment in the form of appropriate assessment so that the development of student learning outcomes not only covers the knowledge aspect only. This research aims to find out the result of students learning outcomes in a group of mathematic learners after being given treatment in the form of performance assessment and self-assessment and find out which treatment gives better results amongst students who are treated in the form of performance assessment and self-assessment. This research is an experimental study. The population taken is all students in grade X of MA Ash-Siddiqiyyah. The sample was taken based on purpose, namely purposive sampling. The class used as the experimental class I is class X IPA 1, which amounted to 30 students, and class X IPS 2, which amounted to 30 students, is experimental class II. Based on the results obtained, the average student learning outcomes in experimental class I is in the high category with an average number gain value of 0.71. The average student learning outcomes in experimental class II are in the medium category and are shown by the average number of gain values of 0.64. Based on the hypothesis test results, the decision is to reject Ho and accept Ha. Then it can be concluded that the results of student learning in the learning group treated by performance assessment are better than student learning outcomes in the learning group treated with self-assessment.